Study on Screening tests among the Blood donors in Community Based Medical College Hospital, Mymensingh, Bangladesh - Begum, Nilufar; Ali, Md Yunus; Haque, Amdadul (Community Based Medical Journal, 2019)
The aim of the study was to find out the prevalence of transfusion transmitted diseases (TTD) in voluntary and Replacement donors. A total of 4,885 donors were analyzed for the prevalence of TTD over a period of 1 year and 9 month from August 2016 to May 2018, Conducted at the Community Based Medical College Hospital, Mymensingh, Bangladesh, of these 38.8% were voluntary donors and 61.2% were replacement donors. Prevalence of Hepatitis B virus (HBv) was highest (.86%) followed by syphilis (.3%), HCV (.14%), Malaria (.06%) and HIV (.04%). Prevalence was more in male replacement donors. Seropositivity of TTD of this study was much lower among blood donors due to proper medical assessment of donors. Pre-donation donor screening procedures is helpful in improving the blood safety and reduces the prevalence of transfusion transmitted diseases. CBMJ 2019 January: vol. 08 no. 01 P: 19-22